Does fluctuating asymmetry of wing traits capture relative environmental stress in a lepidopteran? - Symanski, Cole (Ecol Evol, 2021)
1. Fluctuating asymmetry (FA) is hypothesized to be a useful predictor of population canalization, especially for organisms at risk from environmental change. 2. Identification of traits that meet statistical criteria as FA measures remains a challenge. 3. Here, a laboratory experiment subjected immature butterflies (Vanessa cardui) to diet and temperature conditions of varying stress levels. Variation in dietary macronutrient ratio (protein: carbohydrate) and rearing temperature (optimal: 25°C; elevated: 32°C) was introduced as stressors. Temperature and nutrition are key variables influencing ectotherm growth and fitness and so are likely to be important stressors that influence FA. 4. Individuals subjected to stressful conditions were predicted to show elevated FA of three wing size traits, as well as increased mortality and decreased adult body size. 5. Trait FA did not vary across treatments. Instead, treatment levels impacted viability: The combined incidence of pupal death and expression of significant wing malformations increased in treatment levels designated as stressful. Variation in adult dry mass also reflected predicted stress levels. Results suggest that individuals predicted to display increased FA either died or displayed gross developmental aberrations. 6. This experiment illustrates important constraints on the investigation of FA, including selection of appropriate traits and identification of appropriate levels of stressors to avoid elevated mortality. The latter concern brings into question the utility of FA as an indicator of stress in vulnerable, natural populations, where stress levels cannot be controlled, and mortality and fitness effects are often not quantifiable.